2021
DOI: 10.24854/jpu206
|View full text |Cite
|
Sign up to set email alerts
|

Online learning readiness and well being in Indonesian college students during pandemic: Academic stress as a moderator

Abstract: The pandemic forces students to change their learning process from face to face into online learning. Not all students demonstrate readiness to overcome this pandemic and some of them experience academic pressure. This study aims to investigate whether stress caused by online learning is a moderator of the relationship between online learning readiness and college students’ well-being amid COVID-19 pandemic. Participants of this study were 293 undergraduate students (Mage = 20.42, SD = 1.87) hired using accide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…Penelitian tentang stres pada subjek non klinis khususnya mahasiswa menunjukkan bahwa stres berkorelasi dengan kesiapan belajar dan kesejahteraan psikologis (Akmal & Kumalasari, 2022), regulasi diri dan prokrastinasi akademik (Arwina et al, 2022), kualitas tidur/insomnia (Warella et al, 2022;Nurrachmawati et al, 2022;Ahmad et al, 2022), kecerdasan emosi (Natasia et al, 2022), pola pikir negatif (Pramasasti, 2021), dan motivasi belajar (Setiawati et al, 2022). Oleh karena itu, uji validitas dan reliabilitas pada sampel mahasiswa sangat diperlukan.…”
Section: Dalam Hal Efektivitas Penelitian Telah Banyak Menggunakan Po...unclassified
“…Penelitian tentang stres pada subjek non klinis khususnya mahasiswa menunjukkan bahwa stres berkorelasi dengan kesiapan belajar dan kesejahteraan psikologis (Akmal & Kumalasari, 2022), regulasi diri dan prokrastinasi akademik (Arwina et al, 2022), kualitas tidur/insomnia (Warella et al, 2022;Nurrachmawati et al, 2022;Ahmad et al, 2022), kecerdasan emosi (Natasia et al, 2022), pola pikir negatif (Pramasasti, 2021), dan motivasi belajar (Setiawati et al, 2022). Oleh karena itu, uji validitas dan reliabilitas pada sampel mahasiswa sangat diperlukan.…”
Section: Dalam Hal Efektivitas Penelitian Telah Banyak Menggunakan Po...unclassified
“…Hasil penelitian lain juga menunjukkan prosentase kecemasan yang tinggi di kalangan mahasiswa berdampak terhadap penilaian akhir semester mereka (Moawad, 2020). Dalam hasil penelitian yang pernah dilakukan di Indonesia, menyebutkan bahwa stres akademik pada mahasiswa memiliki pengaruh terhadap kesiapan belajar daring terhadap kesejahteraan psikologis (Akmal & Kumalasari, 2021). Meninjau dari penelitian terdahulu, kesiapan belajar maupun kesejahteraan psikologis merupakan komponen yang penting bagi mahasiswa dalam menampilkan hasil akademik yang mumpuni.…”
Section: Pendahuluanunclassified
“…There is a significant relationship between stress academic and online learning (Samudra & Matulessy, 2021). The results showed that academic stress reduced the positive influence of online learning readiness on student welfare (Akmal & Kumalasari, 2021).…”
Section: Introductionmentioning
confidence: 96%